Model Konseptual Intensi Berwirausaha Berbasis Teknologi Informasi (Ti) - Tjahjono, Heru Kurnianto; Palupi, Majang (Universitas Muhammadiyah Yogyakarta, 2014)
The purpose of this library study is to establish model and propositions that explain intention to be entrepreneur based on information technology (IT). Based on modification of TPB (theory of planned behavior) and TAM (technology acceptance model), this research constructed model intention to be entrepreneur based on information technology. The results produce six propositions that explained antecedents attitude, risk perception, subjective norms and consequences all of these variables.